Auxiliary lasers for Advanced Virgo Gravitational Wave detector using single pass Second Harmonic Generation in Periodically Poled Lithium Niobate crystal. (May 2020) - Khan, I; Genin, E; Fafone, V; Pillant, G; Maggazu, A; Casanueva, J; Chiummo, A; Leroy, N
Abstract: The Advanced Virgo (AdV) detector is composed of different degrees of freedom (DOFs) i.e. Michelson interferometer, two Fabry-Perot arm cavities, signal recycling cavity, and power recycling cavity. These DOFs need to be locked to precise accuracy with robust, fast and reliable control systems. The control signals used to lock all the DOFs are mildly decoupled in frequency and the optical response of the DOFs are nonlinear, where the linear range of operation is just some percentage of the fringe for each DOF, thus posing difficulty in resonance lock at input laser wavelength for all the cavities. In particular, the control status of the arm cavities can alter the state of the detector's operational configuration. Using Auxiliary Lasers to lock the arm cavities at different wavelength offers flexible and robust lock of the detector and more spatial margin on the control signals. Second harmonic generation offers the most direct way to have laser beam with different wavelength and phase locked to the AdV input laser beam. We generated upto 97 mW of SH beam in single configuration at 532 nm using fibered amplified laser source at 1064 nm in a 10 mm long Poled Lithium Niobate crystal.